HOLD-TIME STUDY FOR PHARMACEUTICAL TABLET DURING MANUFACTURING PROCESS: AN INNOVATIVE STEP - Y, SAYEED SHAZIYA; ANJU, GOYAL (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: The objective of the study was to ensure that intermediates and the bulk product can be held without any significant adverse effect on the quality of the material till next step of processing. Such a holding period should be based on data. Studies should not be extended to find the edge of failure for holding. Method: Samples are put away in same natural conditions as in manufacturing/storage. After establishing a sampling plan required sample amount based on the batch size is ascertained, the intervals and tests are to be performed. Samples are kept in a storage container and tested. Results are contrasted and the underlying benchmark information of the control test. Hold-time study data shall give the assurance the maximum allowable hold times for bulk and in-process drug products. In general, one lot can be used for validating hold times if any irregularity comes, results were observed then another two lots can be used for this investigation. Conclusion: Each manufacturing stage shelf life can be determined depending on the hold-time study results. If the hold-time samples are passing at 60-day time point, then the shelf life of the specific stage can be considered up to 45 days.